Analisis Strategi Pemungutan Bea Perolehan Hak Atas Tanah Dan Bangunan Dalam Meningkatkan Penerimaan Pajak Daerah Pada Unit Pelayanan Pemungutan Pajak Daerah Kramat Jati Tahun 2024 - Kemala Sari; Fahrul Anwar Syadat (Jurnal Ilmu Administrasi Publik, 2026)
The failure to achieve the target for Land and Building Acquisition Tax (BPHTB) indicates that the existing collection strategy is not yet optimal in exploring regional tax potential. This study aims to analyze the Land and Building Acquisition Tax (BPHTB) collection strategy in increasing regional tax revenue at the Kramat Jati Regional Development Planning Agency (UPPPPD) in 2024. The research method used a descriptive qualitative approach through in-depth interviews with tax officers, taxpayers, and Notaries/PPATs involved in land and building acquisition transactions. The results show that despite the digitalization of services and efforts to educate taxpayers about taxpayer compliance, optimization of BPHTB revenue remains hampered. This is influenced by several aspects, such as low public literacy, technical constraints in the e-BPHTB system, suboptimal data synchronization between institutions, and perceptions of unfairness regarding applicable rates. Several initiatives have been implemented, such as improving SOPs, accelerating digital services, officer training, active communication with PPAT/BPN, and education on the benefits of BPHTB for regional development. This study concludes that the BPHTB collection strategy has been running quite well, but requires continuous improvement in the aspects of coordination, information transparency, and digital system reliability to be able to contribute maximally to Regional Tax revenue.